10.1515/apf-2017-0005 (Archiv für Papyrusforschung und verwandte Gebiete, 2017)
Abstract This article reviews possible papyrological evidence for rebel activity in the Fayum during the Great Revolt (206-185 BC). A recently-published archive belonging to two Tanis taricheutai has provided evidence for Fayum rebels. Seven further papyri that might describe rebel activity, but have not been read that way before, complement this picture. These documents shed light on the meaning and recognition of violence and crime in a time of revolt.